Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Groundwater dynamics induced by tunneling and reservoir filling at the site of Kala hydropower project - Ao Liu; Ying-Feng Zhang; Yi-Feng Chen; Ran Hu; Zhibing Yang; Jia-Qing Zhou; Hai-Sheng Zheng; Heng-Yi Gan; Bin Chen; En-Ming Zhang (Tunnelling and Underground Space Technology, 2026)

Molecular Mechanism of Absorption, Transport and Metabolic Transformation of Astaxanthin in Aquatic Animals - Huakang Peng; Yihui Du; Qianwen Ding; Dongdong Du; Ruyue Dong; Chao Ran; Zhen Zhang; Yuanyuan Yao; Hui Liang; Ming Li; Nan Wang; Yalin Yang; et al. (Reviews in Aquaculture, 2026)
The global astaxanthin market reached $1.69 billion in 2024, with 47% directed to aquafeed—yet the molecular basis of its absorption, metabolism, deposition, and storage in aquatic organisms remains incompletely resolved. A deeper understanding of these mechanisms will help optimize feed formulations, enhance astaxanthin bioavailability, and improve economic efficiency in aquaculture. This study investigates the absorption mechanisms of astaxanthin mediated by intestinal lipid transporters (SR‐B1, CD36, NPC1L1) and its utilization/deposition in different tissues and organs. It reviews the latest research progress on major absorption pathways, metabolic processes, and storage forms of astaxanthin in aquatic organisms, analyzes key factors affecting its utilization efficiency, and discusses potential future research directions to provide a scientific basis and theoretical support for aquaculture practices.

High-stability active thermal control for nanosatellite payload under multi-timescale disturbances via temperature response decomposition and energy-adaptive error fusion - Qi-Yuan Liu; Yun-Ze Li; Yan-Ao-Ming Xi; Kai-Feng Chang; Ya-Hui Chen; Ran Wei; Yu-Peng Zhou; Xin Zhao (Advances in Space Research, 2026)

Regulation mechanism of N2O and CH4 emissions during the pig manure composting amended with Polygonum Multiflorum Thunb - Ya-jun Duan; Hong-sheng Wu; Jiang-yu Yang; Zheng-tong Zhou; Tao-ran Shi; Cheng Cheng; Zhen-wei Li; Chun-fa Wu; Ming-chun Di; Yu-dong He; Feng-yi Hu (World Journal of Microbiology and Biotechnology, 2026)

A novel passive external surface heat flow balance strategy for high-temperature-stability nano CubeSat thermal design: concepts, models and thermal control effect evaluations - Yan-Ao-Ming Xi; Yun-Ze Li; Qi-Yuan Liu; Kai-Feng Chang; Xin Zhao; Yu-Peng Zhou; Ran Wei (Advances in Space Research, 2026)

Discovery of natural Nopol as promising antibacterial alternative with the capacity to suppress bacterial virulence and enhance plant immunity - Xiao-Di Chen; Yu-Mei Feng; Jun-Ning Ran; Wei Niu; Xin-Ming Yang; Xing-Yu Chen; Xiang Zhou; Song Yang (Pesticide Biochemistry and Physiology, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Tracking high-field-strength-element enrichment pathways in alkaline granites: Insights from potassium and barium isotopes - Hao-Cheng Yu; Zheng-Yu Long; A.E. Williams-Jones; Ralf Halama; Frédéric Moynier; Shan-Shan Li; Ming-Qian Wu; Hao-Ran Duan; Jia-Dong Ma; Nan Ju; Ze-Zhou Wang; Kun-Feng Qiu (Geochimica et Cosmochimica Acta, 2026)

Structure-Oriented Kriging for High-Fidelity Acquisition Footprint Suppression - Liang Huang; Ming-ran Liu; Wen-chao Su; Jiang-yun Zhang; Xu-hui Zhou; Guo-xu Shu; Shou-dong Huo (Applied Geophysics, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Acid and antibiotic stress suppresses soil microbial carbon use efficiency via fungal proliferation: Mechanistic insights from microbial community dynamics - Fengwu Zhou; Xiangmei Zhai; Zongren Dai; Ming Zhou; Ziyi Zhao; Ran Liu; Xinrui Zhang; Shuai Zhang; Zezhen Pan; Wenhui Zhong; Zheng-Shuang Hua; Ming Nie; et al. (Journal of Hazardous Materials, 2025)

Structural characteristics and community formation mechanisms in aquatic plant communities during the near-natural restoration of urban rivers - Yijia Li; Ran Tao; Jie Zhang; Jiafei Zhang; Xiaomeng Zhang; Yunv Dai; Yiping Tai; Yang Yang; Ming Li; Qianhong Xuan; Wenling Zhu; Xinmin Zhou; et al. (Landscape and Urban Planning, 2025)

Strain-specific effects of fish originated Bacillus velezensis on growth, gut health, and disease resistance of zebrafish - Yuan-Yuan Yao; Wen-Hao Zhou; Juan Hu; Ya-Lin Yang; Ming Li; Rui Xia; Chao Ran; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Exploring hydration of air electrodes for protonic ceramic cells: A review - Haosong Di; Zuoqing Liu; Ming Xiao; Yuesheng Bai; Guangming Yang; Zhixin Luo; Wei Wang; Ran Ran; Wei Zhou; Zongping Shao (Chemical Engineering Journal, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Effect of crowding stress on liver health, gut permeability and gut microbiota of genetically improved farmed tilapia (GIFT, Oreochromis niloticus) - Jian Zhang; Jie Chen; Hui Liang; Ming Li; Wenhao Zhou; Yalin Yang; Zhen Zhang; Qianwen Ding; Chao Ran; Zhigang Zhou (Aquaculture, 2025)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Effect of supercritical carbon dioxide on protein structure modification and antimicrobial peptides production of Mongolian cheese and its in vitro digestion - Yawen Geng; Yuanrong Zheng; Ran Zhou; Ming Ma (Food Research International, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Macrophage AHR-TLR4 cross-talk drives p-STAT3 (Ser727)-mediated mitochondrial oxidative stress and upregulates IDO/ICAM-1 in the steatohepatitis induced by aflatoxin B1 - Jing Zhang; Hui Liu; Yang Shen; Dong Cheng; Hui Tang; Qi Zhang; Chao Li; Ming Liu; Wenhuan Yao; Rongrong Ran; Qingzhen Hou; Xiulan Zhao; et al. (Science of The Total Environment, 2024)

2D ZIF-8 derived N-doped porous carbon nanosheets for high-performance Li-Se batteries - Xu-Wei Luo; Ming-Ran Zhou; Mao-Jin Ran; Dao-Xiang Xun; Jia-Le He; Zhi-Yi Hu; Hemdan S.H. Mohamed; Jing Liu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Preliminary assessment of carbonic acid dissociation constants: Insights from observations in China's east coastal oceans - Ping Wang; Qicheng Meng; Liang Xue; Yuhang Zhao; Hao Qiao; He Hu; Qinsheng Wei; Ming Xin; Xiangbin Ran; Chenhua Han; Feng Zhou; Chunying Liu (Marine Environmental Research, 2023)

The effect of stabilized culture of Lactobacillus rhamnosus GCC-3 on gut and liver health, and anti-viral immunity of zebrafish - Hui Liang; Yadong Xie; Ming Li; Jie Chen; Wenhao Zhou; Rui Xia; Qianwen Ding; Yuanyuan Yao; Zhen Zhang; Yalin Yang; Chao Ran; Zhigang Zhou (Fish & Shellfish Immunology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Three new constituents from the Tujia ethnomedicine Swertia punicea Hemsl. - Pan Yi; Bin Li; Salman Zafar; Sajjad Ali; Wen-Bing Sheng; Yu Mao; Fang Zhou; Wen-Ming Chen; Yan-Ran Tang; Cai-Yun Peng; M. Iqbal Choudhary; Atta-ur- Rahman; et al. (Natural Product Research, 2023)

Hyperbranched polyethyleneimine-functionalised chitosan aerogel for highly efficient removal of melanoidins from wastewater - Jia-Yi Tang; Yan-Shu Xiong; Ming-Xing Li; Ran Jia; Li-Shu Zhou; Bo-Huan Fan; Kai Li; Wen Li; Hong Li; Hai-Qin Lu (Journal of Hazardous Materials, 2023)

Dietary supplementation of yeast mannan enhances antiviral immunity of zebrafish (Danio rerio) - Hui Liang; Yadong Xie; Yu Li; Mingxu Xie; Ming Li; Wei Zhou; Jie Chen; Zhen Zhang; Yalin Yang; Chao Ran; Zhigang Zhou (Aquaculture, 2023)

Effect of supercritical carbon dioxide on bacterial community, volatile profiles and quality changes during storage of Mongolian cheese - Jing Feng; Yuanrong Zheng; Xin Zhang; Ran Zhou; Ming Ma (Food Control, 2023)

Paenibacillus hamazuiensis sp. nov., a bacterium isolated from Hamazui hot spring in Yunnan province, south-west China - Juan Wang; Ming Deng; En-Min Zhou; Lei Ran; Cui-Ping Miao; Yi-Qing Li; Jun-Mei Ding; Shu-Kun Tang (Archives of Microbiology, 2022)

Long non‑coding RNA PART1: dual role in cancer - Rui Ran; Chao-Yang Gong; Zhi-Qiang Wang; Wen-Ming Zhou; Shun-Bai Zhang; Yong-Qiang Shi; Chun-Wei Ma; Hai-Hong Zhang (Human Cell, 2022)

Contributions of oceanic and continental AAM to interannual variation in ΔLOD with the detection of 2020–2021 La Nina event - Xue-Qing Xu; Yong-Hong Zhou; Peng-Shuo Duan; Ming Fang; Zhao-Yang Kong; Can-Can Xu; Xian-Ran An (Journal of Geodesy, 2022)
As a strong climate element on interannual scales, the El Nino-Southern Oscillation (ENSO) is a major component of global weather and climate change, and it is also closely related to the interannual atmospheric angular momentum (AAM) and length-of-day changes (ΔLOD). Here, we reprocess and compare the interannual variations of AAM, ΔLOD with ENSO indices, with AAM mass and motion terms calculated over land separately from those over the ocean. Three oscillatory components (at ~ 6, ~ 7, ~ 8 years), due to angular momentum changes in Earth's interior, are removed to obtain the interannual ΔLOD solely related to climatic variations. Our results show that the AAM motion term over the ocean contributes the most to interannual ΔLOD, and that the oceanic AAM has larger variability than that over land, especially during the periods of strong ENSO events. After subtracting contributions associated with interior processes, the interannual ΔLOD anomalies corresponding to extreme ENSO events (1982–1983 ~ 0.43, 1997–1998 ~ 0.36, 2015–2016 ~ 0.42 ms) are about half as strong as those found in previous studies (~ 0.91, ~ 0.76, ~ 0.81 ms). Furthermore, we detect an intermediate La Nina event that occurred from August 2020 to May 2021, forcing the interannual ΔLOD to a minimum value of approximately -0.21 ms.

Research progress on gut health of farmers teleost fish: a viewpoint concerning the intestinal mucosal barrier and the impact of its damage - Hongling Zhang; Chao Ran; Tsegay Teame; Qianwen Ding; Seyed Hossein Hoseinifar; Mingxu Xie; Zhen Zhang; Yalin Yang; Rolf Erik Olsen; Delbert M. Gatlin; Einar Ringø; Ming Duan; et al. (Reviews in Fish Biology and Fisheries, 2020)

Texture and Quality Assessment of Ready-to-eat Farmed Obscure Puffer Fish ( Takifugu obscurus ) Fillet by Evaluating Bacterial and Myofibrillar Degradation and Biochemical Changes during Refrigerated Storage - Ran Zhou; Yuanrong Zheng; Yuan Liu; Ming Ma (Journal of Aquatic Food Product Technology, 2020)

Analysis of nicotine-induced metabolic changes in Blakeslea trispora by GC-MS - Yang Liu; You-ran Shao; Xiang-yu Li; Zhi-ming Wang; Li-rong Yang; Yu-zhou Zhang; Mian-bin Wu; Jian-ming Yao (Journal of Zhejiang University-SCIENCE B, 2020)

Analysis of status and countermeasures of cancer incidence and mortality in China - Chunchun Wu; Mengna Li; Hanbing Meng; Yukun Liu; Weihong Niu; Yao Zhou; Ran Zhao; Yumei Duan; Zhaoyang Zeng; Xiaoling Li; Guiyuan Li; Wei Xiong; et al. (Science China Life Sciences, 2019)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Long-Term (1996–2006) Variation of Nitrogen and Phosphorus and Their Spatial Distributions in Tianjin Coastal Seawater - Shi-tao Peng; Ming-xin Dai; Yandi Hu; Zhi-peng Bai; Ran Zhou (Bulletin of Environmental Contamination and Toxicology, 2009)